Bioinspired Composite, pH-Responsive Sodium Deoxycholate Hydrogel and Generation 4.5 Poly(amidoamine) Dendrimer Improves Cancer Treatment Efficacy via Doxorubicin and Resveratrol Co-Delivery - Tefera Worku Mekonnen; Abegaz Tizazu Andrgie; Haile Fentahun Darge; Yihenew Simegniew Birhan; Endiries Yibru Hanurry; Hsiao-Ying Chou; Juin-Yih Lai; Hsieh-Chih Tsai; Jen Ming Yang; Yen-Hsiang Chang (MDPI AG, 2020)
Maximizing the antitumor efficacy of doxorubicin (DOX) with a new drug delivery strategy is always desired in the field of biomedical science. Because the clinical applications of DOX in the treatment of cancer is limited by the side effects related to the dose. Herein, we report the co-loading of DOX and resveratrol (RESV) using an injectable in situ formed sodium deoxycholate hydrogel (Na-DOC-hyd) at the pH of the tumor extracellular microenvironment. The sequential, controlled, and sustained release of RESV and DOX for synergistic antitumor effects was confirmed by entrapping G4.5-DOX in the RESV-loaded Na-DOC hydrogel (Na-DOC-hyd-RESV). The synergistic antitumor activity of Na-DOC-hyd-RESV+G4.5-DOX was assessed on HeLa cell xenograft tumor in BALB/c nude mice. In the MTT biocompatibility assay, both the G4.5 PAMAM dendrimer and Na-DOC-hyd exhibited negligible cytotoxicity up to the highest dose of 2.0 mg mL−1 in HeLa, MDA-MB-231, and HaCaT cells. The release profiles of DOX and RESV from the Na-DOC-hyd-RESV+G4.5-DOX confirmed the relatively rapid release of RESV (70.43 ± 1.39%), followed by that of DOX (54.58 ± 0.62%) at pH 6.5 in the 7 days of drug release studies. A single intratumoral injection of Na-DOC-hyd-RESV+G4.5-DOX maximally suppressed tumor growth during the 28 days of the treatment period. Na-DOC-hyd-RESV+G4.5-DOX did not cause any histological damage in the major visceral organs. Therefore, this Na-DOC-hydrogel for dual drugs (DOX and RESV) delivery at the pH of the tumor extracellular microenvironment is a promising, safe, and effective combination for antitumor chemotherapy.